2005
DOI: 10.1063/1.2035894
|View full text |Cite
|
Sign up to set email alerts
|

Precise determination of band offsets and chemical states in SiN∕Si studied by photoemission spectroscopy and x-ray absorption spectroscopy

Abstract: We have investigated chemical states and band offsets in SiN∕Si by photoemission spectroscopy and x-ray absorption spectroscopy. N1s photoemission spectra in SiN for three kinds of layer-thickness films are fitted by a single component, suggesting that a nitrogen atom is surrounded by three silicon and nine nitrogen atoms for the first and the second nearest neighbor, respectively. Valence-band offsets between SiN and the Si substrates are determined to be 1.6 eV using valence-band spectra by subtracting the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…It is reported that the peak top of the first derivative XAS spectrum is valid for estimation of conduction band minimum. [13] In the first derivative XAS spectrum of the HfSiON/Si, the peak at 2.5 eV indicates the conduction band minimum for the HfSiON film as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is reported that the peak top of the first derivative XAS spectrum is valid for estimation of conduction band minimum. [13] In the first derivative XAS spectrum of the HfSiON/Si, the peak at 2.5 eV indicates the conduction band minimum for the HfSiON film as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 98%
“…The E v changes by 0.4 eV at a maximum for HfSiON during x-ray irradiation, which is larger compared to that of conventional SiO 2 -based dielectrics. [13] In addition, band offsets of high-k dielectric films are relatively small. Using the band offsets and the dielectric layer thickness for HfSiON in this study and other parameters, [20] the estimated gate leakage increases by about one hundred times when the band offset decreases by 0.4 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…213,214 This difference can be partially attributed to the ultra-low defect densities 215 typically achieved in gate-dielectric-quality SiO 2 and the two times larger bandgap for SiO 2 (∼9 eV) 216 relative to Si 3 N 4 (∼5.5 eV). 217 Interestingly, TAT and FN tunneling have also been reported as the dominant leakage mechanisms in a number of investigations of the electrical properties for Al 2 O 3 films deposited by a variety of methods. 188,[218][219][220] This is consistent with the similar IV characteristics exhibited by the thermal SiO 2 and ALD Al 2 O 3 films in Fig.…”
mentioning
confidence: 99%
“…Time-dependent core-level shifts due to photo-induced carrier-trapping phenomena are reported to be more than 100 meV for various gate insulator films on Si substrates. 10,11 For this reason, we have performed timedependent core-level photoemission analysis during irradiation of incident light source. Sufficient signal-to-noise ratio is obtained in our experimental setup despite the very short data acquisition time for metal/high-k gate stack structures on Si substrates.…”
mentioning
confidence: 99%